Revolutionizing ovarian cancer therapy by drug repositioning for accelerated and cost-effective treatments - Villegas-Vazquez, Edgar Yebran; Marín-Carrasco, Francisco Pável; Reyes-Hernández, Octavio Daniel; Báez-González, Andrea S.; Bustamante-Montes, Lilia Patricia; Padilla-Benavides, Teresita; Quintas-Granados, Laura Itzel; Figueroa-González, Gabriela (Frontiers in Oncology, 2025)
Drug repositioning, the practice of identifying novel applications for existing drugs beyond their originally intended medical indications, stands as a transformative strategy revolutionizing pharmaceutical productivity. In contrast to conventional drug development approaches, this innovative method has proven to be exceptionally effective. This is particularly relevant for cancer therapy, where the demand for groundbreaking treatments continues to grow. This review focuses on drug repositioning for ovarian cancer treatment, showcasing a comprehensive exploration grounded in thorough in vitro experiments across diverse cancer cell lines, which are validated through preclinical in vivo models. These insights not only shed light on the efficacy of these drugs but also expand in potential synergies with other pharmaceutical agents, favoring the development of cost-effective treatments for cancer patients.